A Comparative Study of Refusal to Accept Rights in Iranian Law, Imamiyyah Jurisprudence and Principles of European Contract Law - Seyed Mahdi Mousavi; Amir Sadeghi Neshat (آموزه‌‌های فقه مدني)
Amir Sadeghi Neshat (Associate professor at the University of Tehran) The refusal of the acceptance a right occurs when one party or a third party in a contractual or non-contractual relationship wants to surrender the right to the other party but the other party refuses to accept it except in legal cases, so legislators to protect the other party, that confronted with the refusal of the other party, offering solutions to compensate for his/her losses (damages). In this study, we consider the solutions presented against the refusal to accept the right in Imamiyyah jurisprudence, the Iranian legal system and the principles of European contract law, and by explaining these issues, the similarities and differences of the solutions presented in these three legal systems are studied. The examination of the rules provided for in these three legal systems shows that Imamiyyah jurisprudence and the principles of European contract law tend to apply to self-help sales (non-judicial) institutions, but in the Iranian legal system, reference to the judiciary is accepted as a principle.